Detecting long temporal trends of photosystem II herbicides (PSII) in the Great Barrier Reef lagoon. (April 2022) - Taucare, Grechel; Bignert, Anders; Kaserzon, Sarit; Thai, Phong; Mann, Reinier M.; Gallen, Christie; Mueller, Jochen
Abstract: The Marine Monitoring Program (MMP) was established in 2005 to monitor the inshore health of the Great Barrier Reef (GBR) and evaluate progress towards water quality objectives in Reef Water Quality Improvement Plans. The MMP provides information on the magnitude and spatial extent of pesticide contamination, reports on temporal variability, and provides a risk assessment for the biota in the GBR lagoon. However, long-term trends in pesticide contamination of inshore marine waters over the entire monitoring period (2005–2018) have not been assessed. We used up to 14 years of monitoring data for five PSII herbicides (ametryn, atrazine, diuron, tebuthiuron, and hexazinone) to conduct temporal trend analyses at 11 inshore monitoring sites. The trend analyses suggested increasing significant trends ( p < 0.05) for the five PSII herbicides concentrations at several monitoring sites. Power analysis indicated that monitoring sites with over 10 years of monitoring data had convincing results with 80% power. Highlights: Concentrations of five PSII herbicides in the Great Barrier lagoon have increased between 2005 and 2018. Adjustment for confounding factors 'season' and 'flow' improve the statistical power to detect trends over time. Monitoring sites with over 10 years of monitoring data had convincing results with 80% power.